Application of Audio Visual Assisted Problem-based Learning Model on Problem-solving Ability, and Social Science Learning Motivation - Wijiasih, Runtut; Rusdarti, Rusdarti; Suhandini, Purwadi (JESS (Journal of Educational Social Studies), 2019)
The lecture method using abstract examples makes it difficult for students to understand social studies subject matter. This causes students not to be able to develop potential and passive learning activities. Therefore, effective learning models are needed and can trigger the activeness of students. Problem-based learning (PBL) model and the use of audio-visual media are among the recommended learning models in Curriculum 2013 to improve the quality of learning. The purpose of this study is to examine differences in problem-solving abilities and to learn motivation between students who are given learning using audio-visual aided problem-based learning models, problem-based learning models, and lecture methods (conventional models). This study uses a quasi-experimental design in the form of a non-equivalent control group design. The research population is class VIII students, Public Junior High School 14 Pekalongan City with 242 students, with three sample classes, namely class VIII-C, class VIII-D, and class VIII-E. Based on the pre-test and post-test data, problem-solving ability and motivation questionnaire were statistically processed using the ANOVA test, Fvalue > Ftable, then H1 was accepted while H0 was rejected. The results showed there were differences in problem-solving abilities, and learning motivation between students learning with PBL assisted models with audio-visual, PBL models, and lecture methods.